PENGELOLAAN PENDIDIKAN MORAL SISWA DI SEKOLAH MASA KINI - Rasyid Herbanu Indra Saputra; Alfi Zidanurrohim; Farid Setiawan (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
Education in this era of globalization has had a major impact on Indonesian society in terms of culture and religion. Education in Indonesia has many problems related to the character and personality of students which are very critical and cannot even be controlled by the students themselves. The research method used in this paper is the literary method, by making various literature studies and pieces of literature from experts on the influence of the environment in developing students' Islamic education perspectives. Besides that, this research uses the researcher's self-analysis method, so that insight, knowledge, and the experience of researchers. The results of the study state that the development of education is necessary for the formation of character or morals in the individual personalities of students and educators. Through management is the process of coordinating all resources through the process of planning, organizing, directing and controlling to achieve the goals set.